Physiological responses of children with surgically corrected congenital heart disease during high-altitude trekking: an exploratory observational study - Choi, Kwang Ho; Kim, Woong-Han; Yoon, Ja-Kyoung (Frontiers in Pediatrics, 2026)
BackgroundChildren with surgically corrected congenital heart disease (CHD) are often perceived as fragile and discouraged from engaging in physical activity, despite evidence that structured exercise improves functional capacity and quality of life. However, data on their physiological responses to extreme environments, such as high-altitude exposure, remain limited.MethodsWe conducted an exploratory observational study during an Annapurna Base Camp trek (maximum altitude 4,150 m) in February 2024. Children with surgically corrected congenital heart disease and accompanying healthy adults participated in the expedition. Oxygen saturation (SpO2), heart rate (HR), and blood pressure (SBP and DBP) were recorded daily at sequential altitudes, and adverse events were monitored.ResultsFrom 1,350 m to 4,150 m, SpO2 showed a similar pattern of decline in children (−9.8%) and adults (−8.1%). CHD participants showed a pronounced chronotropic response (+17.8 bpm) with modest declines in both SBP (−9.0 mmHg) and DBP (−5.5 mmHg), while adults showed minimal change. These findings suggest effective cardiovascular adjustment under hypobaric hypoxia and with no evidence of maladaptation or altitude-related illness.ConclusionChildren with surgically corrected CHD showed preserved oxygenation and well-tolerated hemodynamic responses during high-altitude trekking, underscoring their capacity for physiological adaptation when adequately prepared and supervised. The study highlights the feasibility and safety of structured physical challenges for this population and provides preliminary insight into designing exercise programs that promote confidence and participation.